Social Relations in Times of Social Isolation and the Contributions of ICT: Perceptions and Reflections in the Bauru-SP Region - Pompei, David Gustavo (Corporación Universitaria del Caribe, CECAR., 2020)
Due to Covid-19 and social isolation, new ways of relating were adopted through ICT. In this perspective, the objective of this work seeks to discuss how social relationships were impacted by them during the present period, as well as the challenges of social interaction. The methodology included a bibliographic review, field research and analysis of questionnaires applied through a Facebook group. As preliminary results, it was reflected that the local-global crisis brought progress and setbacks. Therefore, ICT contributed to the new configurations of social relationships and interactions in the city of Bauru. It is emphasized that these technologies still do not overcome the interactions developed in the personal sphere.